1997
DOI: 10.1093/humrep/12.11.2534
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of maternal plasma creatine kinase activity as a marker of abnormal early pregnancy

Abstract: We have tested the value of maternal plasma creatine kinase activity for diagnosing ectopic pregnancies obtained after in-vitro fertilization and embryo transfer. Plasma creatine kinase was assayed in 57 patients: 20 normal, 23 miscarriages and 14 ectopic pregnancies, for a total of 240 samples. All values were in the lower part of the normal range except only one in a miscarrying patient. A statistically significant difference was observed for a cut-off value of 45 IU/l between normal and ectopic pregnancies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Maternal CK levels have been previously evaluated in confirmed EP (Korhonen et al, 1996;Qasim et al, 1996;Vandermolen and Borzelleca, 1996;Zorn et al, 1997). CK is a non-specific marker of smooth muscle damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal CK levels have been previously evaluated in confirmed EP (Korhonen et al, 1996;Qasim et al, 1996;Vandermolen and Borzelleca, 1996;Zorn et al, 1997). CK is a non-specific marker of smooth muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…One theory is that damage to the fallopian tube in EP is sufficient to cause an increase in serum Downloaded from https://academic.oup.com/humrep/article-abstract/20/12/3348/2913666 by guest on 13 June 2019 CK (Lavie et al, 1993). Although some studies have demonstrated that maternal serum CK levels can be an important biochemical marker for the diagnosis of EP (Chandra and Jain, 1995;Duncan et al, 1995), the general view is that maternal serum CK concentrations do not reliably predict EP (Korhonen et al, 1996;Qasim et al, 1996;Vandermolen and Borzelleca, 1996;Zorn et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The histopathology of ectopic gestations was not studied in any of the subsequent reports which challenged the findings of Lavie et al 2 , as they showed creatine kinase levels in ectopic pregnancy not to differ from levels observed in controls 3–5 , 7 . Careful reading of these reports can suggest the tubal status of the cases studied.…”
Section: Discussionmentioning
confidence: 94%
“…These investigators reported higher mean creatine kinase levels in ectopic pregnancy compared with controls with normal intrauterine pregnancies or missed abortions, and deduced that creatine kinase levels above a cutoff of 45iu/L were 100% sensitive for the diagnosis of this condition. Their findings, however, could not be reproduced by most subsequent reports 3–5 , while few other studies, which found similarly higher creatine kinase levels in ectopic pregnancy, also pointed out significant overlap with controls, and concluded that creatine kinase was an unreliable marker for ectopic pregnancy 6,7 .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation